2002
DOI: 10.1097/00005768-200212000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Blood volume and hemoglobin mass in endurance athletes from moderate altitude

Abstract: In endurance athletes who are native to moderate altitude, tHb and BV were synergistically influenced by training and by altitude exposure, which is probably one important reason for their high performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
71
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 27 publications
11
71
0
2
Order By: Relevance
“…The over-representation from the Rift Valley mirrors previous findings in elite Ethiopian marathon athletes, where 73% were from the Arsi and Shewa regions proximal to the Rift Valley. Regions proximal to the Rift Valley often lie at altitudes of over 2000 m above sea level, which might be haematologically beneficial in distance running (Schmidt et al, 2002). These findings support suggestions that the success of Kenyan runners is in some way linked to their close proximity to the Rift Valley (Entine, 2001).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The over-representation from the Rift Valley mirrors previous findings in elite Ethiopian marathon athletes, where 73% were from the Arsi and Shewa regions proximal to the Rift Valley. Regions proximal to the Rift Valley often lie at altitudes of over 2000 m above sea level, which might be haematologically beneficial in distance running (Schmidt et al, 2002). These findings support suggestions that the success of Kenyan runners is in some way linked to their close proximity to the Rift Valley (Entine, 2001).…”
Section: Discussionsupporting
confidence: 73%
“…Although equivocal, some studies have concluded that chronic altitude exposure and endurance training, as experienced by many East African runners, combine synergistically to induce haematological adaptations which partially account for their success (Schmidt et al, 2002). A high proportion of elite Ethiopian runners originate from particularly altitudinous regions of Ethiopia (Scott et al, 2003), although this was not necessarily causal to their success.…”
Section: Introductionmentioning
confidence: 99%
“…While Gore et al 12 suggested that world class endurance athletes might have ''maximised'' their total haemoglobin mass after many years of sea level training, Schmidt et al 19 recently reported significantly higher total haemoglobin mass in professional cyclists living at an altitude of 2600 m compared to professional cyclists living at sea level with similar Vo 2max , indicating that there is still potential for a further increase in total haemoglobin mass in sea level endurance athletes if they perform altitude training. The subjects in the present study were elite junior swimmers who undoubtedly still had the potential to increase total haemoglobin mass, whose erythropoiesis was not impaired by insufficient iron availability, and who lived and trained at an altitude high enough for a sufficient hypoxia induced increase in erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Kenyan runners, particularly the international athletes, originate from a distinctive environmental background in terms of geographical distribution and ethnicity (Onywera et al, 2006). Living and training in the highlands of the Great Rift Valley partly contributes to the excellent performance in distance running because of chronic exposure to hypoxic conditions (Schmidt et al, 2002;Wilber & Pitsiladis, 2012). Additionally, athletes had to travel far to school when they were children, commonly by running.…”
Section: Introductionmentioning
confidence: 99%